Analisis Efektivitas Perkuatan Lereng Jalan Menggunakan Simulasi Elemen Hingga - Minmahddun, Anafi (aspal, 2024)
Slope stability represents a major challenge in infrastructure development, particularly in regions with complex geotechnical conditions. This study aims to evaluate the effectiveness of slope stabilization methods using a numerical simulation approach based on the Finite Element Method. The study was conducted on a road section in Southeast Sulawesi, characterized by silty sand soils prone to erosion. Soil investigation data were obtained through cone penetration tests (CPT) to determine soil parameters for the analysis. The slope reinforcement alternatives involve a combination of gravity-type retaining walls (DPT) with mini bore piles and the installation of gabions on riverbanks. The gabions are intended as a long-term mitigation measure to reduce erosion risks on the riverbanks. Simulation results indicate that integrating DPT with mini bore piles enhances slope stability, achieving a safety factor of 1.58 during flood conditions, meeting the minimum criterion of 1.5 according to SNI 8460:2017. Although scouring effects reduce the safety factor to 1.53, this value remains within acceptable limits. The greatest displacement occurs at the toe of the slope but is effectively minimized with the designed reinforcement. This study highlights the importance of the finite element approach in understanding soil-structure interactions. The findings provide practical recommendations for slope reinforcement, especially in areas with high geotechnical risks. Regular monitoring of riverbank erosion is advised to maintain slope stability sustainably.